A dimensão educativa do drama como manifestação da cultura popular de Senador Georgino Avelino-RN - Castro, Denis Silva (2024)
This master's dissertation aimed to investigate the educational dimension of Drama as a cultural manifestation of Senador Georgino Avelino-RN, identifying and discussing the stories and songs of this popular culture, as well as the poetic elements that make up the scenes of its songs. In line with the qualitative nature of the research, conversation was chosen as the research methodology (Sampaio; Ribeiro; Souza, 2023). To this end, seven conversation circles were held with the romancers guardians of Georgino's Drama, from which it was possible to perceive it as an artistic-cultural manifestation with educational potential (especially related to issues of race, gender and ethnicity) woven from popular culture itself, whose knowledge generates knowledge that occurs through orality and the artistic expression present in the dance-staging of this game. In this sense, it is possible to affirm that the educational dimension of Drama as a cultural manifestation of Senador Georgino Avelino-RN resides not only in the speeches of the romancers and in the lyrics of the songs that tell stories, but also in the poetics that involve the elements of their scenes (costumes, props, colors, dances, rhythms...), to the extent that they bring with them an expression of the body that plays, and that, by playing, resists amidst the silencing of dissident cultures.